Friction properties of polyvinylidene fluoride with added MoS2 nanotubes. Issue 11 (24th September 2013) - Remskar, Maja; Jelenc, Janez; Visic, Bojana; Varlec, Ana; Cesarek, Maja; Krzan, Andrej
<x xml:space="preserve">Abstract</x> The MoS2 nanotubes (NTs) were added to polyvinylidene fluoride (PVDF) with the aim to adjust its friction properties. Thin films and thin nanocomposite coatings were prepared with different MoS2 NT concentrations. Morphology and distribution of the NTs inside the nanocomposites were studied by optical and electron microscopy. Raman spectroscopy performed before and after friction tests was used to evidence partial transformation of PVDF into piezoelectric phase due to friction caused drawing. Friction tests in flat‐on‐flat and ball‐on‐disk configuration with AISI 316 stainless steel as counterpart revealed a strong reduction of coefficient of friction.